Sustain GEOBIM—a New Method to Simulate Sustainable Development Scenarios for Urban Areas - Heinz J. Bernegger; Patrick Laube; Pascal Ochsner; Mihaela Meslec; Hanno Rahn; Johann Junghardt; Isabella Aurich; Simon Ashworth (Circular Economy and Sustainability, 2021)
In 2015, 193 member states of the United Nations (UN) signed the 2030 Agenda, entitled “Transforming Our World: The 2030 Agenda for Sustainable Development,”. The planned implementation by 2030, leaves only a decade to realize the 17 Sustainable Development Goals (SDG). Municipalities and cities constitute important stakeholders, who are obliged under SDG 11, to find ways to develop realistic solutions. Implementation and strategic planning require, among other things, new instruments to digitally model various sustainable development scenarios. Currently, however, it is still unclear what has to be modelled and how. What is clear is that sustainability and digitalization have to come together to deliver results. Several key challenges need to be overcome. First, is the heterogeneity of existing data and documents used in the built environment. Future solutions will depend on a combination of Building Information Modelling (BIM) and Geographic Information System (GIS). Second, is the merging of different existing data on an adequate level of abstraction which allows practical use of GIS and BIM data in a common model. Third, is the development of functioning, cost-effective workflows that will enable broad applications which adequately simulate specific sustainability aspects using spatial and temporal scenarios. This paper shows how these challenges can be systematically addressed in practice. It demonstrates which aspects of sustainability can be made visible and comprehensible for all stakeholders using only one single BIM- and GIS based data model. The proposed workflow could thus be considered as the basis for planning the next generation of smart and sustainable cities.

Smart Sustainable Cities of the New Millennium: Towards Design for Nature - Chiara Catalano; Mihaela Meslec; Jules Boileau; Riccardo Guarino; Isabella Aurich; Nathalie Baumann; Frédéric Chartier; Pascale Dalix; Sophie Deramond; Patrick Laube; Angela Ka Ki Lee; Pascal Ochsner; et al. (Circular Economy and Sustainability, 2021)
Urban environments consist of a mosaic of natural fragments, planned and unintentional habitats hosting both introduced and spontaneous species. The latter group exploits abandoned and degraded urban niches which, in the case of plants, form what is called the third landscape . In the Anthropocene, cities, open spaces and buildings must be planned and designed considering not only human needs but also those of other living organisms. The scientific approach of habitat sharing is defined as reconciliation ecology , whilst the action of implementing the ecosystem services and functioning of such anthropogenic habitats is called Urban Rehabilitation . However, urban development still represents the main cause of biodiversity loss worldwide. Yet, the approach of planners and landscape architects highly diverges from that of ecologists and scientists on how to perceive, define and design urban green and blue infrastructure. For instance, designers focus on the positive impact that nature (generally associated with indoor and outdoor greeneries) has on human well-being, often neglecting ecosystems’ health. Instead, considering the negative impact of any form of development and to achieve the no net loss Aichi’s objectives, conservationists apply mitigation hierarchy policies to avoid or reduce the impact and to offset biodiversity. The rationale of this review paper is to set the fundamentals for a multidisciplinary design framework tackling the issue of biodiversity loss in the urban environment by design for nature . The method focuses on the building/city/landscape scales and is enabled by emerging digital technologies, i.e., geographic information systems, building information modelling, ecological simulation and computational design.